2018
DOI: 10.1103/physrevb.97.155121
|View full text |Cite
|
Sign up to set email alerts
|

Resonant tunneling across a ferroelectric domain wall

Abstract: Li, M.; Tao, L. L.; Velev, J. P.; and Tsymbal, Evgeny Y., "Resonant tunneling across a ferroelectric domain wall" (2018 Motivated by recent experimental observations, we explore electron transport properties of a ferroelectric tunnel junction (FTJ) with an embedded head-to-head ferroelectric domain wall, using first-principles density-functional theory calculations. We consider a FTJ with La 0.5 Sr 0.5 MnO 3 electrodes separated by a BaTiO 3 barrier layer and show that an in-plane charged domain wall in the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…28,32 Our follow-up theoretical work has demonstrated that a headto-head DW structure in LSMO/BTO/LSMO FTJs was induced by polar interfaces, and the resonant tunneling mechanism through the confined electron gas was confirmed by quantum-transport calculations, revealing strongly enhanced conductance of the DW-FTJ. 33 We found, however, that the total energy of the DW state was higher than that of the uniform polarization (UP) state, indicating that the DW state was metastable. This behavior was consistent with the experimental observations by Sanchez-Santolino et al, 28 who found that once a DW was destroyed by applying a sufficiently large electric field, it could not be restored.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…28,32 Our follow-up theoretical work has demonstrated that a headto-head DW structure in LSMO/BTO/LSMO FTJs was induced by polar interfaces, and the resonant tunneling mechanism through the confined electron gas was confirmed by quantum-transport calculations, revealing strongly enhanced conductance of the DW-FTJ. 33 We found, however, that the total energy of the DW state was higher than that of the uniform polarization (UP) state, indicating that the DW state was metastable. This behavior was consistent with the experimental observations by Sanchez-Santolino et al, 28 who found that once a DW was destroyed by applying a sufficiently large electric field, it could not be restored.…”
mentioning
confidence: 68%
“…It partly screens the polarization charge at both interfaces and controls the electron density of the two-dimensional electron gas (2DEG), which partly screens the polarization charge at the head-to-head DW. 33 A simple model based on the electrostatic energy of the FTJ, being determined by the ionic surface charge density at the two interfaces, the polarization charge density at the interfaces and DW, the band offset between the electrodes and ferroelectric, the formation of the 2DEG at the DW, and screening in the electrodes, allows a reasonable fit of the DFT results, as shown in Fig. 1(c The formation of the energy minima at the DW and UP states can be analyzed using a polarization-dependent energy profile.…”
Section: mentioning
confidence: 99%
“…This confinement drives energy quantization of electronic states in the well and affects the electron tunneling current of the device. Experiments below 100 K reveal conductance oscillations in the measured tunneling current and point to resonant transport through discrete unoccupied electronic states confined to the wall [4,184]. The measured energy gap between almost equally spaced discrete levels was around 70–90 meV.…”
Section: Solid-state Domain Wall Device Conceptsmentioning
confidence: 99%
“…The measured energy gap between almost equally spaced discrete levels was around 70–90 meV. Quantum transport calculations [184] further found resonant tunneling through confined electronic states as an orbital selective process and suggest the use of domain walls embedded in MTJs as an alternative avenue to affect electronic transport at the nanoscale.…”
Section: Solid-state Domain Wall Device Conceptsmentioning
confidence: 99%
“…The above application is generally based on uniform polarization states in FTJs, but recent investigations also reported non-uniform polarization states in FTJs, [3][4][5][6] especially in multiferroic tunnel junctions (MFTJs) with ferromagnetic electrodes. 7,8 FTJs and MFTJs with non-uniform polarization states also have potential applications in a variety of devices such as domain wall memories 9 and resonant tunneling transistors, 10,11 which expand their applications to broader elds.…”
Section: Introductionmentioning
confidence: 99%